Security and privacy assurance in advancing technologies : new developments - Nemati, Hamid R., 1958- (Hershey, PA : Information Science Reference, 2011)
"This book provides a comprehensive collection of knowledge from experts within the field of information security and privacy and explores the changing roles of information technology and how this change will impact information security and privacy"--Provided by publisher.
Includes bibliographical references (p. 401-439) and index.
Keywords: Information technology -- Security measures; Management -- Technological innovations